High-capacity rechargeable sodium ion button cell and preparation method thereof
By designing high-capacity rechargeable sodium ion buckle battery, using fibrosis and pressure-treated electrode films, traditional button batteries have solved the problems of low voltage platform, poor overdischarge capacity and complex process, and achieved high-capacity and 2-digital The effect of secondary charge and discharge and simplification of the process.
Patent Information
- Application Number
- CN202411461132.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional ML and LIR button batteries have defects in terms of low voltage platform, poor overdischarge capability, complex process technology and high cost and insufficient durability, which is difficult to meet the market's demand for high-capacity and rechargeable batteries.
Using a high-capacity rechargeable sodium ion buckle battery design, including a positive electrode shell, a positive electrode self-supporting film, a diaphragm, an negative electrode self-supporting film, an negative electrode shell and electrolyte, the electrode film is prepared by fibrosis and rolling pressure treatment of air flow crusher to simplify the process And improve battery performance.
A high-capacity, secondary charge and dischargeable sodium ion buckle battery is realized, with a high voltage platform, simplifying the process process, reducing costs, and improving the overdischarge capability and cycling performance of the battery.
Smart Images

Figure CN119481228A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion button batteries, and in particular to a high-capacity rechargeable sodium ion button battery and a preparation method thereof. Background Art
[0002] Currently, the mainstream micro button batteries in the market are mainly ML and LIR, both of which have good cycle stability and safety, are relatively environmentally friendly, and can be widely used in small portable electronic devices such as watches, calculators, remote controls, etc.
[0003] Patent technical document CN202410652941.7 discloses a lithium primary battery and a preparation method thereof. The lithium primary battery provided by the invention has good safety performance and energy density, and well solves the problem of difficulty in injecting liquid in the preparation process of traditional lithium primary batteries, improves production efficiency, and effectively improves the interface compatibility between the electrolyte layer and the electrode, so that the electrolyte layer and the electrode are in close contact, thereby extending the life of the lithium primary battery and reducing the self-discharge of the lithium primary battery; Patent technical document CN201180019719.4 discloses a lithium iron phosphate with an olivine crystal structure and a lithium secondary battery using the lithium iron phosphate. The olivine-type lithium iron phosphate is not easily separated by being coated with a uniform thin film on the surface of the lithium iron phosphate, and exhibits excellent conductivity and density, because carbon is coated on the particle surface of the lithium iron phosphate in a state in which the amount of carbon released in water is significantly small.
[0004] However, with the continuous advancement of science and technology, traditional ML and LIR have also exposed some shortcomings. For example, the main disadvantage of ML is that it is a primary battery with a low voltage platform and poor over-discharge capability. The main disadvantage of LIR is that the cell manufacturing process is complicated, usually a winding or folding process, and also involves a welding process, which greatly increases the process cost. In addition, LIR batteries still have the common problems of lithium-ion batteries, that is, the battery's over-discharge resistance is poor. When discharged below the cut-off potential, the electrode material structure collapses or the SEI decomposes abnormally, leading to battery failure. In areas with storage or over-discharge requirements, ML and LIR cannot meet market demand well. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a high-capacity rechargeable sodium ion button battery and a preparation method thereof, so as to provide a sodium ion button battery with high capacity and capable of secondary charge and discharge.
[0006] Based on the above purpose, the present invention provides a high-capacity rechargeable sodium ion button battery, including a positive electrode shell, a positive electrode self-supporting film, a separator, a negative electrode self-supporting film, a negative electrode shell, and an electrolyte; The steps for preparing the positive electrode self-supporting film are as follows: S11: After the positive electrode active material, the conductive agent and the binder are evenly mixed, the dry mixed powder is placed in a jet mill for fiberization; S12: rolling the fiberized material, and then cutting it into pieces with a diameter of 12-14 mm, which is a positive electrode self-supporting film; The steps for preparing the negative electrode self-supporting film are as follows: S21: After the negative electrode active material, the conductive agent and the binder are evenly mixed, the dry mixed powder is placed in a jet mill for fiberization; S22: rolling the fiberized material, and then cutting it into pieces with a diameter of 14-16 mm, which is a negative electrode self-supporting film; Preferably, the positive and negative electrode shells are the positive and negative electrode shells used in conjunction with CR2016.
[0007] Preferably, the inner bottom of the positive electrode shell is coated with a conductive coating with a thickness of 1 μm.
[0008] Preferably, the diaphragm is one of a PP / PE diaphragm and a glass fiber diaphragm.
[0009] Preferably, the solute of the electrolyte is NaPF6, and the solvent is one or more of PC, DMC, DEC, and EC.
[0010] Furthermore, the electrolyte is NaPF6 / DC+EMC.
[0011] Preferably, the weight percentages of the positive electrode active material, the conductive agent, and the binder in step S11 are 80%-95%: 2%-10%: 3%-10%.
[0012] Preferably, the positive electrode active material in step S11 is one of layered oxides, polyanions and Prussian blue.
[0013] Preferably, the conductive agent in step S11 is one of conductive carbon black, carbon nanotubes and Ketjen black.
[0014] Preferably, the binder in step S11 is PTFE.
[0015] Preferably, in step S21, the weight percentages of the negative electrode active material, the conductive agent, and the binder are 80%-96%: 2%-10%: 2%-10%.
[0016] Preferably, the negative electrode active material in step S21 is one of soft carbon and hard carbon.
[0017] Preferably, the conductive agent in step S21 is one of conductive carbon black, carbon nanotubes, Ketjen black, and KS-6.
[0018] Preferably, the binder in step S21 is PTFE.
[0019] Preferably, the working parameters of the air flow mill are: air intake pressure of 0.3-1.5 MPa, turbine speed of 300-650 rpm, and time of 10-15 min.
[0020] Preferably, the rolling pressure is 5-100T.
[0021] Furthermore, the present invention also provides a method for preparing a high-capacity rechargeable sodium ion button battery, and the specific preparation steps are as follows: Assemble the positive electrode shell, positive electrode self-supporting film, separator, negative electrode self-supporting film and negative electrode shell in order from bottom to top, inject electrolyte, and finally seal with a button-type sealing machine.
[0022] Beneficial effects of the present invention: The high-capacity rechargeable sodium ion button battery of the present invention can be charged and discharged twice and has a higher voltage platform.
[0023] The high-capacity rechargeable sodium ion button battery of the present invention has a simple manufacturing process, does not require complex processes such as winding and folding, and does not require complex assembly equipment.
[0024] The high-capacity rechargeable sodium ion button battery of the present invention has no current collector design, utilizes the characteristics of the dry-hair electrode self-supporting film, the electrode can be in direct contact with the shell, has excellent over-discharge capability, and the battery can still circulate normally when over-discharged to 0V voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description. Figure 1 This is an assembly sequence diagram of the sample obtained in Example 2 of the present invention; Figure 2 This is the first charge and discharge curve of the sample obtained in Example 2 of the present invention; Figure 3 The charge-discharge curve diagram of the sample obtained in Example 2 of the present invention during the cycle; Figure 4 This is a cycle curve diagram of the sample obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0027] Example 1: A high-capacity rechargeable sodium ion button battery, the specific preparation steps are as follows: (1) After 80 g of sodium manganese vanadium phosphate, 10 g of conductive carbon black and 10 g of PTFE were mixed evenly, the dry mixed powder was placed in a jet mill for fiberization to obtain a fiberized material, wherein the working parameters of the jet mill were: inlet pressure of 0.3 MPa, turbine speed of 300 rpm, and time of 10 min; (2) rolling the fiberized material and then cutting it into pieces with a diameter of 12 mm to obtain a positive electrode self-supporting film, wherein the rolling parameter is 5T; (3) After 80 g of hard carbon, 10 g of conductive carbon black and 10 g of PTFE were mixed evenly, the dry mixed powder was placed in a jet mill for fiberization to obtain a fiberized material, wherein the working parameters of the jet mill were: inlet pressure of 0.3 MPa, turbine speed of 300 rpm, and time of 10 min; (4) rolling the fiberized material and then cutting it into pieces with a diameter of 14 mm to obtain a negative electrode self-supporting film, wherein the rolling parameter is 25T; (5) A 1 μm thick conductive carbon black layer was applied to the inner bottom of the positive electrode shell. The positive electrode shell, positive electrode self-supporting film, separator, negative electrode self-supporting film, and negative electrode shell were then assembled in order from bottom to top and filled with NaPF6 / DC+EMC electrolyte. Finally, a CR2016 button sealer was used to seal the assembled sample to obtain a high-capacity rechargeable sodium-ion button battery.
[0028] Example 2: A high-capacity rechargeable sodium ion button battery, the specific preparation steps are as follows: (1) After 88 g of sodium manganese vanadium phosphate, 6 g of conductive carbon black and 6 g of PTFE were mixed evenly, the dry mixed powder was placed in a jet mill for fiberization to obtain a fiberized material, wherein the working parameters of the jet mill were: inlet pressure of 0.9 MPa, turbine speed of 550 rpm, and time of 13 min; (2) rolling the fiberized material and then cutting it into pieces with a diameter of 13 mm to obtain a positive electrode self-supporting film, wherein the rolling parameter is 45T; (3) After 88 g of hard carbon, 6 g of conductive carbon black and 6 g of PTFE were mixed evenly, the dry mixed powder was placed in a jet mill for fiberization to obtain a fiberized material. The working parameters of the jet mill were as follows: inlet pressure of 0.9 MPa, turbine speed of 550 rpm and time of 13 min. (4) rolling the fiberized material and then cutting it into pieces with a diameter of 15 mm to obtain a negative electrode self-supporting film, wherein the rolling parameter is 50T; (5) A 1 μm thick conductive carbon black layer was applied to the inner bottom of the positive electrode shell. The positive electrode shell, positive electrode self-supporting film, separator, negative electrode self-supporting film, and negative electrode shell were then assembled in order from bottom to top and filled with NaPF6 / DC+EMC electrolyte. Finally, a CR2016 button sealer was used to seal the assembled sample to obtain a high-capacity rechargeable sodium-ion button battery.
[0029] Example 3: A high-capacity rechargeable sodium ion button battery, the specific preparation steps are as follows: (1) After 95 g of sodium manganese vanadium phosphate, 2 g of conductive carbon black and 3 g of PTFE were mixed evenly, the dry-mixed powder was placed in a jet mill for fiberization to obtain a fiberized material, wherein the working parameters of the jet mill were: inlet pressure of 1.5 MPa, turbine speed of 650 rpm, and time of 15 min; (2) rolling the fiberized material and then cutting it into pieces with a diameter of 14 mm to obtain a positive electrode self-supporting film, wherein the rolling parameter is 75T; (3) After 96 g of hard carbon, 2 g of conductive carbon black and 2 g of PTFE were mixed evenly, the dry-mixed powder was placed in a jet mill for fiberization to obtain a fiberized material. The operating parameters of the jet mill were: inlet pressure of 1.5 MPa, turbine speed of 650 rpm, and time of 15 min. (4) rolling the fiberized material and then cutting it into pieces with a diameter of 16 mm to obtain a negative electrode self-supporting film, wherein the rolling parameter is 100T; (5) A 1 μm thick conductive carbon black layer was applied to the inner bottom of the positive electrode shell. The positive electrode shell, positive electrode self-supporting film, separator, negative electrode self-supporting film, and negative electrode shell were then assembled in order from bottom to top and filled with NaPF6 / DC+EMC electrolyte. Finally, a CR2016 button sealer was used to seal the assembled sample to obtain a high-capacity rechargeable sodium-ion button battery.
[0030] Comparative Example 1: A button-type sodium ion battery, the specific preparation steps are as follows: (1) 88g of sodium manganese vanadium phosphate, 6g of conductive carbon black and 6g of PTFE were mixed and then ball-milled. After ball-milling for 6h, the obtained slurry was evenly coated on aluminum foil using an automatic coating machine, dried in a 60°C blast drying oven for 2h, and then placed in a 80°C vacuum drying oven for 12h. Finally, the slurry was cut into pieces with a diameter of 13mm, which was the positive electrode sheet; (3) 88 g of hard carbon, 6 g of conductive carbon black and 6 g of PTFE were mixed and evenly milled. After ball milling for 6 h, the obtained slurry was evenly coated on aluminum foil using an automatic coating machine, dried in a 60°C forced air drying oven for 2 h, and then placed in a 80°C vacuum drying oven for 12 h. Finally, the slurry was cut into pieces with a diameter of 15 mm, which was the negative electrode sheet. (5) A 1 μm thick layer of conductive carbon black was applied to the inner bottom of the positive electrode shell, and then the positive electrode shell, positive electrode sheet, separator, negative electrode sheet, and negative electrode shell were assembled in order from bottom to top, and filled with NaPF6 / DC+EMC electrolyte. Finally, a CR2016 button sealer was used to seal the assembled sample to obtain a button-type sodium-ion battery.
[0031] Comparative Example 2: A button-type sodium ion battery, the specific preparation steps are as follows: (1) 88g of sodium iron phosphate, 6g of conductive carbon black and 6g of PTFE were mixed and then ball-milled. After ball-milling for 6h, the obtained slurry was evenly coated on aluminum foil using an automatic coating machine, dried in a blast drying oven at 60°C for 2h, and then placed in a vacuum drying oven at 80°C for 12h. Finally, the pieces were cut into pieces with a diameter of 13mm, which were the positive electrode sheets. (3) 88 g of hard carbon, 6 g of conductive carbon black and 6 g of PTFE were mixed and evenly milled. After ball milling for 6 h, the obtained slurry was evenly coated on aluminum foil using an automatic coating machine, dried in a 60°C forced air drying oven for 2 h, and then placed in a 80°C vacuum drying oven for 12 h. Finally, the slurry was cut into pieces with a diameter of 15 mm, which was the negative electrode sheet. (5) A 1 μm thick layer of conductive carbon black was applied to the inner bottom of the positive electrode shell, and then the positive electrode shell, positive electrode sheet, separator, negative electrode sheet, and negative electrode shell were assembled in order from bottom to top, and filled with NaPF6 / DC+EMC electrolyte. Finally, a CR2016 button sealer was used to seal the assembled sample to obtain a button-type sodium-ion battery.
[0032] Performance Testing The sample obtained in Example 2 was subjected to charge and discharge cycle test: Charge to 4.2V at a charging rate of 0.1C, then discharge to 2.5V at a discharging rate of 0.1C, stand for 10 minutes, cycle 10 times, and observe the cycle curve; Charge to 4.2V at a charging rate of 0.1c, then discharge to 0V at a discharging rate of 0.1c. After standing for 10 minutes, charge to 4.2V at a charging rate of 0.5c, and then discharge to 2.5V at a discharging rate of 0.5c. Repeat 100 cycles and observe its cycle curve.
[0033] from Figure 2 , 3 , Figure 4It can be seen that the button battery of the present invention can perform normal charge and discharge cycles, and after the battery is subjected to an over-discharge test, it still has excellent cycle performance. When the number of cycles reaches 77, the capacity retention rate can still be maintained at more than 85%.
[0034] The charge and discharge tests were carried out on Example 2 and Comparative Examples 1 and 2. The test results are shown in Table 1: Table 1 Performance test results Capacity (mAh / g) The capacity retention rate after 77 cycles (%) Example 2 258.1 85.4 Comparative Example 1 225.6 86.7 Comparative Example 2 201.4 84.8 Data analysis: From Table 1, it can be seen that the high-capacity rechargeable sodium ion button battery of the present invention can be made into a thick electrode and can form a supporting membrane property by using a dry electrode process. Compared with the traditional button battery, it does not require a current collector, and the electrode material is directly in contact with the shell. The process is simpler, and its cycle performance is not much different from that of the traditional button battery, and the capacity is larger.
[0035] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A high-capacity rechargeable sodium-ion button battery, characterized in that: It includes a positive electrode shell, a positive electrode self-supporting film, a separator, a negative electrode self-supporting film, a negative electrode shell, and an electrolyte; The steps for preparing the positive electrode self-supporting film are as follows: S11: After the positive electrode active material, the conductive agent and the binder are evenly mixed, the dry mixed powder is placed in a jet mill for fiberization; S12: rolling the fiberized material, and then cutting it into pieces with a diameter of 12-14 mm, which is a positive electrode self-supporting film; The steps for preparing the negative electrode self-supporting film are as follows: S21: After the negative electrode active material, the conductive agent and the binder are evenly mixed, the dry mixed powder is placed in a jet mill for fiberization; S22: rolling the fiberized material, and then cutting it into pieces with a diameter of 14-16 mm to obtain a negative electrode self-supporting film.
2. The high-capacity rechargeable sodium ion button battery according to claim 1, characterized in that: The inner bottom of the positive electrode shell is coated with a conductive coating with a thickness of 1 μm.
3. The high-capacity rechargeable sodium ion button battery according to claim 1, characterized in that: The diaphragm is one of a PP / PE diaphragm and a glass fiber diaphragm.
4. The high-capacity rechargeable sodium ion button battery according to claim 1, characterized in that: The solute of the electrolyte is NaPF6, and the solvent is one or more of PC, DMC, DEC, and EC.
5. The high-capacity rechargeable sodium ion button battery according to claim 1, characterized in that: The weight percentages of the positive electrode active material, the conductive agent, and the binder in step S11 are 80%-95%: 2%-10%: 3%-10%.
6. The high-capacity rechargeable sodium ion button battery according to claim 1, characterized in that: The weight percentages of the negative electrode active material, the conductive agent, and the binder in step S12 are 80%-96%: 2%-10%: 2%-10%.
7. The high-capacity rechargeable sodium ion button battery according to claim 1, characterized in that: The working parameters of the air flow mill are as follows: air inlet pressure is 0.3-1.5MPa, turbine speed is 300-650rpm, time is 10-15min, and roller pressure is 5-100T.
8. A method for preparing a high-capacity rechargeable sodium ion button battery according to any one of claims 1 to 7, characterized in that: The specific preparation steps are as follows: Assemble the positive electrode shell, positive electrode self-supporting film, separator, negative electrode self-supporting film and negative electrode shell in order from bottom to top, inject electrolyte, and finally seal with a button-type sealing machine.
Citation Information
Patent Citations
Lithium iron phosphate of olivine crystal structure and lithium secondary battery using same
CN102844916A
Lithium primary battery and preparation method thereof
CN118610503A